Telenursing Dalam Perawatan Kanker: Tinjauan Literatur Sistematis Tentang Perawatan Suportif, Manajemen Gejala, Dan Hasil Pasien - Putra Gibran, Arya Ramadhan; Widitiara, Soibah; Novitasari, Dwi; Ma'rifah, Atun Raudotul (Seminar Nasional Penelitian dan Pengabdian Kepada Masyarakat 2025, 2025)
Introduction: Cancer patients often experience complex, ongoing physical and psychosocial needs that extend beyond clinical treatment settings. Telenursing has emerged as a promising intervention to deliver continuous, patient-centered care through digital platforms. Objectives: This systematic review aims to evaluate the effectiveness of telenursing interventions in improving supportive care, symptom management, functional outcomes, satisfaction, and cost-efficiency in cancer care. Methods: This review followed PRISMA guidelines and included studies published between 2015 and 2025 from databases such as PubMed, Scopus, ProQuest, ScienceDirect, Wiley, and Jane Journal. Keywords included “telenursing,” “tele-nursing,” and “cancer,” using MeSH terms. A total of 38 studies were included after screening and quality appraisal using the Jadad scale for randomized controlled trials. Results: Telenursing interventions demonstrated significant benefits in reducing supportive care needs, especially in psychological, physical, and informational domains. Several studies reported improved symptom control, including pain, fatigue, and chemotherapy-induced side effects, as well as enhanced functional recovery in post-surgical patients. High levels of patient satisfaction and reduced healthcare utilization were noted, particularly in studies that incorporated structured, nurse-led follow-up and digital tools. Despite these promising outcomes, heterogeneity in study design and limited methodological rigor in some trials constrain the generalizability of results. Conclusion: Telenursing offers a feasible, cost-effective, and patient-centered approach to enhance cancer care across diverse populations and settings. Future research should prioritize high-quality trials, equity in digital access, and long-term outcomes to support sustainable integration into oncology nursing practice.